CYP3A7*1C allele: linking premenopausal oestrone and progesterone levels with risk of hormone receptor-positive breast cancers - Johnson, Nichola; Maguire, Sarah; Morra, Anna; Kapoor, Pooja Middha; Tomczyk, Katarzyna; Jones, Michael E; Schoemaker, Minouk J; Gilham, Clare; Bolla, Manjeet K; Wang, Qin; Dennis, Joe; Ahearn, Thomas U; et al. (Springer Science and Business Media LLC, 2021)
Epidemiological studies provide strong evidence for a role of endogenous sex hormones in the aetiology of breast cancer. The aim of this analysis was to identify genetic variants that are associated with urinary sex-hormone levels and breast cancer risk.